2021
DOI: 10.3390/cancers13205059
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Ras/MAPK Signaling Research and Targeting in Blood and Solid Cancers

Abstract: The mitogen-activated protein kinase (MAPK) pathway, consisting of the Ras-Raf-MEK-ERK signaling cascade, regulates genes that control cellular development, differentiation, proliferation, and apoptosis. Within the cascade, multiple isoforms of Ras and Raf each display differences in functionality, efficiency, and, critically, oncogenic potential. According to the NCI, over 30% of all human cancers are driven by Ras genes. This dysfunctional signaling is implicated in a wide variety of leukemias and solid tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 329 publications
(393 reference statements)
2
48
0
Order By: Relevance
“…KRAS mutation constitutively results in the activation of the mitogen-activated protein kinase (MAPK) signaling pathway, which subsequently activates downstream substrates, leading to the expression of genes involved in cellular proliferation, differentiation, and survival. As targeted inhibitors of the MAPK pathway have been approved to treat several types of KRAS -mutated carcinoma [ 44 ], it is worth investigating the therapeutic significance of MAPK inhibitors for patients with MLA. In fact, the effect on growth suppression of MAPK pathway inhibition in ovarian carcinoma cells was more profound in tumors harboring KRAS mutation than in KRAS wild-type tumors [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…KRAS mutation constitutively results in the activation of the mitogen-activated protein kinase (MAPK) signaling pathway, which subsequently activates downstream substrates, leading to the expression of genes involved in cellular proliferation, differentiation, and survival. As targeted inhibitors of the MAPK pathway have been approved to treat several types of KRAS -mutated carcinoma [ 44 ], it is worth investigating the therapeutic significance of MAPK inhibitors for patients with MLA. In fact, the effect on growth suppression of MAPK pathway inhibition in ovarian carcinoma cells was more profound in tumors harboring KRAS mutation than in KRAS wild-type tumors [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been demonstrated the anti‐apoptotic effect of the PI3K–Akt–mTOR signal transduction pathway, namely, regulating the activity of Bcl‐2 family members and transcription factor nuclear factor‐kappa B (NF‐κB), and inhibiting the activation of aspartate‐specific cysteine protease family members, the activity of GSK3, the expression of pro‐apoptotic genes, mitochondria from releasing cytochrome c, and activity of the TRAIL (TNF‐related apoptosis‐inducing ligand) receptor (Akbarzadeh et al, 2021; Kaboli et al, 2021; Peng et al, 2022; Sun et al, 2021; Yu et al, 2021). The MAPK signaling pathway exists in many cells across almost all the organisms, and includes ERKs, JNKs, and p38 (Dillon et al, 2021). ERKs are mainly related to cell proliferation and differentiation (Pashirzad et al, 2021; Sugiura et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose is one of the main members in the glycol- (Akbarzadeh et al, 2021;Kaboli et al, 2021;Peng et al, 2022;Sun et al, 2021;Yu et al, 2021). The MAPK signaling pathway exists in many cells across almost all the organisms, and includes ERKs, JNKs, and p38 (Dillon et al, 2021). ERKs are mainly related to cell proliferation and differentiation (Pashirzad et al, 2021;Sugiura et al, 2021).…”
Section: Integrative Analysis Of Docetaxel Based On the Metabolic And...mentioning
confidence: 99%
“…Growth factor receptors, such as the TGF-β receptors EGFR, VEGFR, PDGFR, FGFR, and IG-IR, can all activate RAS and downstream RAF and MEK. Ras proteins act as molecular switches that control the activation and regulation of related pathways that are responsible for numerous cell behaviors [62]. The study with selected inhibitors against the targets in this cascade has shown positive results, such as growth inhibition, anti-angiogenesis, and suppressed metastasis in cancer cell lines and animal models.…”
Section: Ras/raf/mapk Signaling Pathwaymentioning
confidence: 99%